Open‐label, multicenter study of self‐administered icatibant for attacks of hereditary angioedema. Issue 3 (March 2014) - Aberer, W.; Maurer, M.; Reshef, A.; Longhurst, H.; Kivity, S.; Bygum, A.; Caballero, T.; Bloom, B.; Nair, N.; Malbrán, A.
Abstract Background Historically, treatment for hereditary angioedema (HAE) attacks has been administered by healthcare professionals (HCPs). Patient self‐administration could reduce delays between symptom onset and treatment, and attack burden. The primary objective was to assess the safety of self‐administered icatibant in patients with HAE type I or II. Secondary objectives included patient convenience and clinical efficacy of self‐administration. Methods In this phase IIIb, open‐label, multicenter study, adult patients were trained to self‐administer a single 30‐mg icatibant subcutaneous injection to treat their next attack. Icatibant‐naïve patients were treated by an HCP prior to self‐administration. Evaluations included adverse event (AE) reporting, a validated questionnaire for convenience, and visual analog scale for efficacy. Results A total of 151 patients were enrolled; 104 had an attack requiring treatment during the study, and 97 patients (19 naïve) were included in the self‐administration cohort. Recurrence or worsening of HAE symptoms (22 of 97) was the most commonly reported AE; rescue medications including icatibant (N = 3) and C1‐inhibitor concentrate (N = 6) were used in 13 cases. Overall, 89 of 97 patients used a single injection of icatibant. No serious AEs or hospitalizations were reported. Most patients (91.7%) found self‐administration preferable to administration in the clinic. The median time to symptom relief (3.8 h) was comparable with results from controlled trials of icatibant. Conclusions With appropriate training, patients were successfully able to recognize HAE attacks and decide when to self‐administer icatibant. This, coupled with the patient‐reported high degree of satisfaction, convenience and ease of use supports the adoption of icatibant self‐administration in clinical practice.